Iron Age Settlement and Cemetery at Sejlflod in Himmerland, North Jutland - Nielsen, Jens N. (Journal of Danish Archaeology, 1982)
Iron Age Settlement and Cemetery at Sejlflod in Himmerland, North Jutland